Place-name politics in multilingual areas : a comparative study of Southern Carinthia (Austria) and the Tešín/Cieszyn Area (Czechia) /: a comparative study of Southern Carinthia (Austria) and the Tešín/Cieszyn Area (Czechia). (2021) - Jordan, Peter; Mácha, Přemysl; Balode, Marika; Krtička, Luděk; Obrusník, Uršula; Pilch, Pavel; Sancho Reinoso, Alexis
No abstract available